Trading Patients: Applying the Alternative Model for Personality Disorders to Two Cases of DSM-5 Borderline Personality Disorder Over Time and Across Therapists - Bliton, Chloe F.; Rosenstein, Lia K.; Pincus, Aaron L. (Frontiers in Psychology, 2022)
The DSM-5 Alternative Model for Personality Disorders (AMPD) dimensionally defines personality pathology using severity of dysfunction and maladaptive style. As the empirical literature on the clinical utility of the AMPD grows, there is a need to examine changes in diagnostic profiles and personality expression in treatment over time. Assessing these changes in individuals diagnosed with borderline personality disorder (BPD) is complicated by the tendency for patients to cycle through multiple therapists over the course of treatment leaving the potential for muddled diagnostic clarity and disjointed case conceptualizations. Following patient trajectories across therapists offers a unique opportunity to examine the AMPD’s sensitivity to and utility for capturing personality stability and change over time for patients with BPD. This paper demonstrates the utility of the AMPD for two clinical cases in three distinct ways: i) highlighting heterogeneity in BPD between patients, ii) comparing improvements in personality severity and style over time, and iii) elucidating profile change across therapist ratings. We present two patients diagnosed with DSM-5 Section II BPD, crossing between two therapists over the course of 3 years of psychodynamic psychotherapy. Treating clinicians rated patients for their respective treatment phases using the Level of Personality Functioning Scale (LPFS), capturing severity, and the Personality Inventory for the DSM-5 (PID-5), capturing style. AMPD diagnostic profiles differentiated patients with BPD in both severity and style, and captured within-patient change beyond within-therapist response bias. Results indicated greater improvements in personality severity while personality style remained more stable. Implications for the patients’ treatment progress and associated challenges are discussed, as are considerations for the utility of the AMPD in therapy.